Kelayakan Komposit Pet Daur Ulang Berpenguat Talc Resin Sebagai Bahan Filamen 3D - Verdy Banarma; Sugianto Sugianto; Hasdiansah Hasdiansah (Jurnal Inovasi Teknologi Terapan, 2026)
This study aims to utilize used PET plastic waste as a basic material for 3D filaments with the addition of talc resin as a reinforcing material. Literature review shows that talc resin can increase stiffness and mechanical strength in polymer composites. The experimental process was carried out through mixing, molding, and tensile and impact tests according to ASTM standards. The test results showed that the addition of 10% talc resin provided optimal tensile strength and toughness compared to other varia tions. Thus, filaments based on used plastic and talc resin are suitable for use in environmentally friendly 3D printing applications.